2010
DOI: 10.1117/12.847025
|View full text |Cite
|
Sign up to set email alerts
|

Towards ultimate optical lithography with NXT:1950i dual stage immersion platform

Abstract: Optical lithography, currently being used for 45-nm semiconductor devices, is expected to be extended further towards the 32-nm and 22-nm node. A further increase of lens NA will not be possible but fortunately the shrink can be enabled with new resolution enhancement methods like source mask optimization (SMO) and double patterning techniques (DPT). These new applications lower the k1 dramatically and require very tight overlay control and CD control to be successful. In addition, overall cost per wafer needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…As laser interferometer measurements are based on the optical wavelength of the laser, uncompensated changes in the refractive index of air in the optical path lead to measurement noise and error. In addition, frequent high acceleration and de-acceleration of wafer stages cause unwanted air flow and cause non-uniformity in air pressure/temperature/humidity/ composition [25,187], and thus contribute to repeatability error and noise. It has been experimentally demonstrated that the 2D encoder solution can achieve 0.2 nm measurement noise (3s), in comparison to 0.8 nm measurement noise (3s) by laser interferometers [25].…”
Section: Semiconductor Manufacturing Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As laser interferometer measurements are based on the optical wavelength of the laser, uncompensated changes in the refractive index of air in the optical path lead to measurement noise and error. In addition, frequent high acceleration and de-acceleration of wafer stages cause unwanted air flow and cause non-uniformity in air pressure/temperature/humidity/ composition [25,187], and thus contribute to repeatability error and noise. It has been experimentally demonstrated that the 2D encoder solution can achieve 0.2 nm measurement noise (3s), in comparison to 0.8 nm measurement noise (3s) by laser interferometers [25].…”
Section: Semiconductor Manufacturing Equipmentmentioning
confidence: 99%
“…In addition, frequent high acceleration and de-acceleration of wafer stages cause unwanted air flow and cause non-uniformity in air pressure/temperature/humidity/ composition [25,187], and thus contribute to repeatability error and noise. It has been experimentally demonstrated that the 2D encoder solution can achieve 0.2 nm measurement noise (3s), in comparison to 0.8 nm measurement noise (3s) by laser interferometers [25]. Another advantage of the 2D planar encoder solution is that it is less expensive than laser interferometer solutions which provide six-axis position feedback.…”
Section: Semiconductor Manufacturing Equipmentmentioning
confidence: 99%
“…Defect data was collected from more than 700 wafers during Factory Acceptance Tests (FAT) from more than 70 NXT:1950i dual stage immersion scanners [4]. The defect detection scheme [5] included printing 45-nm lines and 55-nm spaces onto 300-mm wafers (full wafer coverage).…”
Section: A Defect Monitoringmentioning
confidence: 99%
“…Only recently, it became possible to design a planar encoder system with a sufficient resolution to operate as the long-range measurement system of a wafer scanner as schematically shown in figure 15 [11]. Its main advantage is the short path through air of less than 15 mm, reducing the thermal sensitivity by a factor of 100 to DL/L = 10 −8 per degree Celsius.…”
Section: (C) Long-range Incremental Measurement Systemmentioning
confidence: 99%